Factors influencing dietary compliance amongst Australian diabetics - Andrews, Elizabeth *; Ong, Derek Lai Teik *; Summers, Jane; Woodside, Frances (2017)
Managing the socio-economic burdens associated with the exponential global growth of diabetes diagnosis, poses one of the greatest challenges to modern health systems. Whilst there is no known cure for diabetes, many of the negative health impacts can be successfully minimised through formal therapy, dietary modification and exercise. In particular, dietary modification is considered an important first step and crucial for positive diabetes management and therapy outcomes. Despite this knowledge and extensive support and education provided by the health system, diabetes educators report that many people with diabetes are unable or unwilling to practice recommended dietary modification. This study empirically tests a model of factors that have been shown to play a role in influencing dietary compliance and confirms the importance of self-efficacy in this behaviour. The findings of this study are translated using a social marketing framework into recommendations for diabetes health educators.